A single-center retrospective cohort study on the efficacy and safety of temporary endoscopic nasobiliary drainage in patients with unresectable malignant biliary obstruction with endoscopic biliary stent - Huan Liu; Chuanke Shi; Zhideng Yan (BMC Surgery)
Abstract Background Endoscopic biliary stent (EBS) is the preferred palliative treatment for patients with unresectable malignant biliary obstruction (MBO). We tried endoscopic nasobiliary drainage (ENBD) within 2 weeks after EBS to improve the adverse events and stent patency time after endoscopic retrograde cholangiopancreatography (ERCP). Methods A total of 285 eligible patients with unresectable MBO were divided into EBS group and EBS + ENBD group. Clinical outcomes and adverse events were compared. Results The EBS + ENBD group (n = 74) was similar to the EBS group (n = 211) in clinical characteristics and improvement in liver function after ERCP. The two groups were also similar in terms of stent clinical success rate, incidence of postoperative cholangitis, postoperative bleeding and postoperative pancreatitis. 69 patients in the EBS group and 10 patients in the EBS + ENBD group were followed up continuously. The results showed that the EBS + ENBD group was higher than the EBS group in terms of stent patency time (246.1 days, 95% CI, 141.3–351.0 days vs. 195.3 days, 95% CI, 163.0-227.5 days; P = 0.420), but it was not statistically significant. Conclusion For patients with unresectable MBO, compared with EBS alone, ENBD placement after EBS for temporary biliary drainage may improve liver function and reduce adverse events.